IMPLEMENTASI PEMBELAJARAN BERBASIS HOTS (HIGH ORDER THINKING SKILL) DI SEKOLAH DASAR KOTA MALANG - Wicaksono, Antonius; Bagus Sugiharto, Firsta (STKIP Subang, 2021)
HOTS (High Order Thinking Skill) is material used by the students for helping the achievement of the competency standard , the purpose of education of primary and competence have (Depdiknas.2006) This study aims to describe the implementation of learning based on High Order Thinking Skills (HOTS) in Elementary Schools in Malang. It is well known that the implementation of the 2013 curriculum suggests that the importance of applying HOTS to the learning process in elementary schools. Therefore, it is necessary to conduct a study in the form of research to see the effectiveness of its implementation in elementary school. This research is a descriptive study with a qualitative approach. There are 2 methods used, namely descriptive and evaluative methods. The study population was all elementary schools in Malang. The research sample there are 40 public elementary schools in all districts in Malang. Data was collected using interview guidelines, observation sheets, and documentation. The results showed: (1) the average level of success of teachers in formulating HOTS-based learning planning in SD Malang only reached 79.46 even though it was in the Good category. (2) The average success rate of the implementation of HOTS-based learning as a whole is at 74.81% with the Fair category. (3) The average success rate of HOTS-based authentic assessment formulation in SD Malang is at 74.65% with the Fair category. Thus, improvement efforts are still needed, especially those related to the implementation of learning and authentic assessment of HOTS-based learning in Malang Primary School.